Demoralization as a form of teacher burnout - Sokal, Laura; Eblie Trudel, Lesley (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
Over fifty years of research investigating teacher burnout has resulted in a well-accepted model of burnout that involves three dimensions: exhaustion, depersonalization, and loss of accomplishment. Recently, a new cause of teacher attrition has been proposed called “demoralization,” on the argument that demoralization is a distinct phenomenon from burnout. In light of new research methodologies that allow for examination of unique pathways or “profiles” of teacher burnout, we explore the question, providing an analysis that suggests instead that depersonalization can be fairly represented as one profile of burnout.